Screening and genotyping of group B streptococcus in pregnant and non-pregnant women in Turkey - Alp, Feyza; Findik, Duygu; Dagi, Hatice Turk; Arslan, Ugur; Pekin, Aybike Tazegul; Yilmaz, Setenay Arzu (The Journal of Infection in Developing Countries, 2016)
Introduction: The purpose of this study was to investigate group B streptococcus (GBS) colonization, to compare the methods, to determine the relationship between GBS carriage and risk factors, and to genotype the GBS isolates. Methodology: Recto-vaginal swab specimens were obtained from 500 women, and a questionnaire was administered to each to assess their risk factors for GBS carriage. A culture, GBS antigen test, and polymerase chain reaction (PCR) were performed on all samples. Antibiotic susceptibility testing was performed, and the clonal relationship was determined by pulsed-field gel electrophoresis (PFGE) on all viable isolates. Results: Of the 500 women, sixty-eight (13.6%) women were GBS carriers, of whom 9.8% were pregnant and 16.5% not. There was a significant difference between GBS carriage and history of premature rupture of membrane (PROM). GBS was isolated from 65 (13%) samples. GBS was positive in 70 (14%) samples by antigen test and in 62 (12.4%) by PCR. Sixty-eight of the 70 positive antigen tests were confirmed by PCR or culture. Fifty-five isolates were resistant to tetracycline, 16 to erythromycin and clindamycin, and 13 to levofloxacin. Thirteen different pulsotypes and 17 sporadic strains were determined by PFGE. Conclusions: GBS carriage rate in non-pregnant women was higher than in pregnant women. The GBS antigen test was more sensitive than culture and PCR. GBS isolates did not originate from a single clone and contained sporadic strains. There was a significant difference between GBS carriage and history of PROM. Epidemiologic data obtained in this study will help future studies.